2008
DOI: 10.3170/2008-8-18369
|View full text |Cite
|
Sign up to set email alerts
|

Exploring spatiotemporal patterns in early stages of primary succession on former lignite mining sites

Abstract: Questions: 1. Does random colonization predominate in early stages of primary succession? 2. Do pioneer species facilitate the establishment of later arriving species? 3. Does an initially random distribution change to an aggregated pattern with ongoing succession? Location: Lignite mining region of Lower Lusatia, eastern Germany. Methods: Individual plants were mapped along a 2 m × 28 m transect during three successive years and classified into two groups (1) the pioneer Corynephorus canescens and (2)‘all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 71 publications
2
28
1
Order By: Relevance
“…The aggregated patterns found in subzone El are similar to those observed in other stressful environments such as semi-arid shrublands (Rayburn et al, 2011) and savannas (Schleicher et al, 2011), and high-mountain communities (Fajardo et al, 2008). We also detected an increase in aggregation over the study period, as found by Malkison and Kadmon (2007), and Felinks and Wiegand (2008) in early successional communities. On the contrary, we found that the pattern of new recruited individuals was independent of (subzone El), or showed repulsion to (subzones El and E3), surviving individuals (Fig.…”
Section: Erosional Subzonessupporting
confidence: 66%
See 4 more Smart Citations
“…The aggregated patterns found in subzone El are similar to those observed in other stressful environments such as semi-arid shrublands (Rayburn et al, 2011) and savannas (Schleicher et al, 2011), and high-mountain communities (Fajardo et al, 2008). We also detected an increase in aggregation over the study period, as found by Malkison and Kadmon (2007), and Felinks and Wiegand (2008) in early successional communities. On the contrary, we found that the pattern of new recruited individuals was independent of (subzone El), or showed repulsion to (subzones El and E3), surviving individuals (Fig.…”
Section: Erosional Subzonessupporting
confidence: 66%
“…This has been possible because over the first few years of succession spatial point patterns of pioneer species markedly change (Malkison and Kadmon, 2007;Felinks and Wiegand, 2008), particularly in regions of tropical climate, where this process is rapid . However, the examination of other processes, such as facilitation of juvenile pioneer trees by mature ones (Nishimura and Kohyama, 2002), may require longer time frames or a space-for-time substitution approach (Walker et al, 2010a).…”
Section: Limitationsmentioning
confidence: 99%
See 3 more Smart Citations